Modulation of non-radiative recombination in organic-inorganic halide perovskites for light emission - Nur Fadilah Jamaludin (Nanyang Technological University, 2020)
Metal halide perovskites (MHPs) have garnered extensive attention from the scientific community since its inception as a light harvester in 2009. With a general formula of ABX3, where the monovalent A-site cation is surrounded by four corner-sharing BX6 metal halide octahedra, solar cells based on this material (PSCs) have shown remarkable efficiencies owing to their superior optoelectronic properties. Research on MHP-based LEDs (PeLEDs) has made tremendous progress following early reports on light emission in 2014, with current state-of-the-art devices exhibiting external quantum efficiencies exceeding 20%. However, industrialization of PeLED is not without challenges, with performance, reliability, and scalability; all contingent towards advancing the fundamental understanding of these materials and their light-emitting characteristics.